The concept of land alienation practice between Malaysia and Indonesia / Najihah Azhar - Azhar, Najihah (2020)
Every country has own land rule which commonly relate with land application concept as this research focused in land alienation registration perspective. It means by land procedure or framework of land registration. For this research, land alienation is the process in getting an ownership on any land. The title basically contains two sets of related information. Means that, who owns the land and where it belongs. In order to enhance social, physical, economic and spatial imbalance, each country has land policies and land planning systems. Land policy provides the framework, direction and continuity of land-based decision-making when implementing national development plans involving countries, countries and regional plans. In Malaysia and Indonesia, the government implements land policies in a wider supervisory framework. Both for the purposes of the annual tax amount, the information contained therein applies conditions and restrictions to ensure that the owner is aware of what they can and cannot do. The land must be measured, and boundary signs must be planted on it before the land title is registered with the individual ownership of the land, it can avoid any fraud or misappropriation, especially in terms of land dealing. This research of comparative study approaches to application concept in Malaysia and Indonesia into land alienation respective use a methodology a judicial normative approach to law by referring to the related policies and department of land. Besides, this research proved by getting the feedback from various focus group like Land and Mine Office (PTG), Malaysia’s Survey and Mapping (JUPEM), and Licensed Land Surveyor randomly. It called verbal communication which the respondent specifically answered. From this, can figured out prediction for this research issues like determine the concept of legislation of two countries, identify the department and policies involved, analyse the procedure and forms included in land registration management system. So that, can gain some information and great sharing from these four focus groups. Then, can get the confident level of from each focus group who are agree with this research issues which lead to improve for better land registration management based on the respected current legislation for both countries, Malaysia and Indonesia.